1984
DOI: 10.1111/j.1476-5381.1984.tb16217.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular reactivity in diabetes mellitus: possible role of insulin on the endothelial cell

Abstract: The response to vasoactive agents of microvessels of the rat was tested in vivo by direct microscopic observation of the exteriorized mesentery and assessment of cutaneous vascular permeability changes with Evans blue. The constrictor response to a standard amount of noradrenaline in mesenteric microvessels was fully antagonized by acetylcholine in normal, diabetic, adrenalectomized and diabetic‐adrenalectomized rats. In contrast, the minimum doses of histamine or bradykinin, effective in normal or adrenalecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
7

Year Published

1988
1988
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 23 publications
2
36
0
7
Order By: Relevance
“…Both mammals and viruses encode apparently nonsignaling receptors that may sequester chemokines, preventing their actions on target cells. In addition, proteoglycans that can bind all chemokines, both at the cell surface and as part of the extracellular matrix, may be important regulators of chemokine function (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Both mammals and viruses encode apparently nonsignaling receptors that may sequester chemokines, preventing their actions on target cells. In addition, proteoglycans that can bind all chemokines, both at the cell surface and as part of the extracellular matrix, may be important regulators of chemokine function (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…This is still a controversial point as other investigators have suggested a direct correlation between hyperglycemia and the incidence of infection in diabetic patients (Rayfield et al 1982). A number of studies shows that diabetic animals present a decreased response to intradermally administered bradykinin and vasoactive amines as well as swelling induced by dextran, carrageenan, and cellulose sulphate, indicating alteration in the microcirculatory reactivity (Garcia-Leme et al 1974, Fortes et al 1984, Akamine et al 2003. Moreover, neutrophils from diabetics have also been shown to present functional abnormalities such as less phagocytizing capacity (Wertman & Henney 1962) and chemotactic responses (Mowat & Baum 1971, Fortes et al 1991, Mello et al 1992, which might be extended to other inflammatory cells as those involved in allergic processes.…”
mentioning
confidence: 99%
“…Before starting the experiment, the laser was calibrated using a 2-W Broadband Power/Energy Meter (model 13 PEM 001/J). The laser fluence on the rat skin was 10 J/cm 2 , corresponding to an irradiated area of 0.025 cm 2 and an exposure time of 17 sec. Wounds were irradiated at only one point, at their central region.…”
Section: Laser Irradiationmentioning
confidence: 99%
“…Complications include impaired wound healing, circulatory alterations, decreased collagen production, and skin defects. [1][2][3][4][5] It has been suggested that diabetes mellitus causes macro-and microvascular alterations, as well as neurological diseases. Some authors have demonstrated that lowlevel laser therapy (LLLT) stimulates wound healing, by increasing collagen deposition and blood flow in the wound area.…”
Section: Introduction Dmentioning
confidence: 99%